Does Omega-3 supplementation decrease carotid intima-media thickening in hemodialysis patients? - Mohammad Hossein Kajbaf; Fariborz Khorvash; Mojgan Mortazavi; Shahrzad Shahidi; Firoozeh Moeinzadeh; Ziba Farajzadegan; Shahnaz Amani Tirani (Wolters Kluwer Medknow Publications, 2016)
Objective: A randomized, double-blind, placebo-controlled clinical trial was performed to assess the effect of omega-3 supplementation (3 g/day) on atherosclerosis progression by measuring carotid intima-media thickness (cIMT) in hemodialysis (HD) patients. Methods: A total of 54 HD patients were randomized into two groups: Intervention group (n = 27), in which patients were given 3 g/day omega-3 for 6 months and placebo group (n = 27), in which patients received placebo using the same administration protocol. All patients underwent a carotid artery ultrasound scan to measure cIMT at baseline and at 6 months. Findings: cIMT decreased significantly in omega-3 group (0.79 ± 0.21 mm at baseline vs. 0.65 ± 0.18 mm at 6 months, P< 0.001). On the other hand, a nonsignificant increase in cIMT was seen in placebo group (0.75 ± 0.17 mm at baseline vs. 0.79 ± 0.17 mm at 6 months, P = 0.12). Moreover, cIMT was statistically significantly different between omega-3 and placebo groups at 6 months (P < 0.001). After 6 months, a statistically significant increase was observed in high-density lipoprotein level in omega-3 group compared to placebo group (P = 0.03). Urea reduction ratio was also statistically significantly higher in omega-3 than placebo group at 6 months (P = 0.03). No significant difference was observed in terms of other variables between the two groups. Conclusion: These data suggested that omega-3 supplementation plays a protective role in the progression of atherosclerosis in HD patients.